Struktura rynku prywatnych ubezpieczeń zdrowotnych w Unii Europejskiej - Kiełbasa, Monika (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The author describes types of insurers selling VHI in the European Union and examines the extent to which VHI is purchased by groups rather than by individuals. Voluntary health insurers in the European Union can be distinguished in terms of their legal status and in terms of their degree of specialization in health. In terms of legal status, three types of insurers are present in the EU market for VHI: mutual and provident associations (distinguished by their non-profit status) and commercial companies (distinguished by their for-profit status). Germany is the only member state in which substitutive VHI is sold entirely by specialist health insurers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 458-468